الأحكام الموضوعية للجرائم الانتخابية في التشريع الجزائري - إدريس, قرفي (Sciences humaines; Vol. 33 (2014): SCIENCES HUMAINES, 2014)
الانتخاب يعد دعامة أساسية لنظام الحكم الديمقراطي باعتباره وسيلة للمشاركة في تكوين حكومة تستمد وجودها في السلطة واستمراريتها من إسنادها إلى الإرادة الشعبية، ومن هذا المنطلق كان لابد من إحاطة العملية الانتخابية بمجموعة ضمانات تحفظ لها نزاهتها وحسن سيرها في مختلف مراحلها.       وهذا ما دفع بأغلبية المشرعين عند وضعهم لقوانين الانتخابات إلى تجريم بعض الأفعال التي من شأنها المساس بحرية ونزاهة تلك العملية؛ وهو ما اصطلح عليه بالجرائم الانتخابية.       حيث تشكل الجريمة الانتخابية إحدى الظواهر الخطرة التي تهدد كيان المجتمع برمته، كونها تمس البنيان السياسي والديمقراطي، لذلك وجب تلافي وقوعها بتظافر الجهود للمساهمة في العمل الوقائي ضد الجريمة الانتخابية.   There is no doubt that the election considered as a basic base for the democratic ruling system as a mean in participating in forming a government that grasp its existence in the authority and continuity from its reliance on the public will, and as such had to be briefed of the electoral process set guarantess the reservation with integrity and good functioning in various stages.          And this is why the majority of when lawmakers and the status of the election laws defining and criminalizing certain acts which could affect the freedom and integrity of that process and this is what has been termed electoral crimes.         Where the electoral crime is one of the electoral dangerous phenomena that threaten society as a whole entity, as it is effecting the political and democratic structure through the breaches of the electoral process, for that should be moving in the inside of each right and cannot over come without falling in the circle of responsibility.